Analisis Keberhasilan Usaha Kecil dan Dampaknya Terhadap Pendapatan Keluarga di Kota Jambi - Fahrizal Fahrizal (Ekonomis: Journal of Economics and Business, 2020)
The roles of small enterprises in supporting economic growth, either covering locally or nationally, may not be taken for granted. It is proven by the fact that when Indonesia was stricken by an economic crisis the small enterprises relatively stable. In reality, however, they have been facing many problems, one of which is the source of found/capital. In addition, they also lack basic skills in financial and business management. Generally, most of them are secondary school graduates. In Jambi, the number of small and medium enterprises reaches 2730 with 35.950 employees employed. Such a number is already potentially sufficient to improve the economic growth of the region. Thus, a study regarding the existence of small enterprises in Jambi should be conducted. The study itself should mainly be focused on the problems found in running such kind of enterprises. A study was conducted in December 2015 to February 2016 in Jambi city, taking the cases from the Jelutong subdistrict. The objects of the study were small enterprises including grocery stores. Snacks shops, and furniture depots. The variables studied included the successes of small enterprises (enterprise volume), household income rates, entrepreneurial experiences, educational levels, domestic expenditures, and access to the bank. Based on the result of the study, it is acknowledged that capitals and educational levels strongly determine the success of small enterprises. Therefore, to boots, their involvement in Jambi city, especially at the Jelutung subdistrict, support from related institutions are essentially needed. Such support may include improving the small entrepreneurs’ knowledge and skills in business and financial management. Besides, the source of found/capital should also be taken into account.